2021
DOI: 10.1186/s12875-021-01425-9
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and health status differences among primary healthcare professionals in Portugal

Abstract: Background This paper is focused on two indicators which may be considered as proxies of individuals’ well-being: self-assessed health and burnout intensity. There is little research relating these concepts with the type of the primary healthcare setting, its urbanization density and the region. The aims of this work are threefold: (i) to find determinant factors of individual health status and burnout, (ii) to find possible differences across different types of health care units, differently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
(69 reference statements)
0
5
0
2
Order By: Relevance
“…Im Rahmen der ersten COVID-19-Pandemiewelle (März–April 2020) wurde insbesondere in stark von der COVID-19-Pandemie betroffenen Ländern von einem großen Überforderungserleben von medizinischem Personal berichtet 1 2 3 . Vor allem die Angst vor eigener Ansteckung sowie die Angst vor Ansteckung naher Angehöriger wurden von medizinischem Personal als sehr belastend empfunden 4 5 .…”
Section: Hintergrundunclassified
“…Im Rahmen der ersten COVID-19-Pandemiewelle (März–April 2020) wurde insbesondere in stark von der COVID-19-Pandemie betroffenen Ländern von einem großen Überforderungserleben von medizinischem Personal berichtet 1 2 3 . Vor allem die Angst vor eigener Ansteckung sowie die Angst vor Ansteckung naher Angehöriger wurden von medizinischem Personal als sehr belastend empfunden 4 5 .…”
Section: Hintergrundunclassified
“…Contrary to previous meta-analyses that included physicians of all specialties [4,41], other healthcare professionals [39], or mixed interventions [42], we circumscribed our analysis only to MBIs and PHCP. Therefore, these results are only applicable to PHCP, which allows making specific inferences about the effectiveness of MBIs on a sector highly vulnerable to burnout [8][9][10][11][12]. Another strength of our review is related to the methodological design.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Burnout is a three-dimensional syndrome characterized by high emotional exhaustion, high depersonalization, and a diminished sense of personal accomplishment [7]. This symptom is highly prevalent among primary healthcare professionals (PHCP) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Although no studies have been found that explicitly evaluated burnout differences between urban and rural nurses in the United States, rural nurses and physicians in Spain had higher burnout in Spain, 10 whereas in Portugal, researchers found no differences in burnout between urban and rural nurses. 11 To classify the demand for acute care RNs throughout the state, in 2019, chief nursing officers (CNOs) participated in a survey about their needs for RNs. 12 CNOs reported a high demand for and difficulty filling RN positions at their facilities.…”
Section: We Carementioning
confidence: 99%